ANALISIS IMPLEMENTASI KESELAMATAN PASIEN DI PUSKESMAS KOTA SURABAYA DITINJAU DARI ENAM SASARAN KESELAMATAN PASIEN - Bernadeta Lintang Hardy; Sutopo Patria Jati; Yuliani Setyaningsih (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
Patient safety is one of the important elements of a health service system that is effective and efficient in improving the quality of health services. Public health center as a first-level health facility must be able to improve the quality of health services to the maximum, especially on patient safety indicators, so that accreditation status can increase. However, the development of patient safety issues in Indonesia, especially at the public health center level, is not as dynamic as hospitals and the reporting of patient safety incidents at public health center is still not transparent, especially in Indonesia. This research method uses qualitative research with a case study approach. Data collection was carried out using in-depth interview techniques and secondary data collection. The implementation of the patient safety program has been running well in accordance with the Policy / SOP contained in Permenkes 11 Th.2017 by adjusting the needs of the public health center. In addition, in the implementation of patient safety, several obstacles were found, such as insufficient human resource needs, the absence of special budgeted funds, minimal facilities and infrastructure, ineffective communication between officers so that miscommunication occurred, and human error. So, it is necessary to evaluate DKK Surabaya in relation to human resources, funds, facilities, and infrastructure, as well as the need to update the standards / guidelines in Permenkes related to patient safety standards. Finally, there is a need for an IKP data transparency policy, especially in public health center.